PLUM FRUGIVOROUS PHEROMONE TRAP RESULTS OF MONITORING (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In this article, information on the results of monitoring the development of plum frugivores using a pheromone trap in the conditions of the Tashkent region is presented.